Pendidikan Akhlak Digital: Upaya Mencegah Cyberbullying melalui Pembelajaran Kreatif Pembuatan Poster pada Mata Pelajaran Akidah Akhlak di MTs Sumbersari Kowang - Nashihah, Siti Roudlotun; Masrufah, Luluk Iddah; Achoita, Ana (Indo-MathEdu Intellectuals Journal, 2025)
The rapid development of digital technology has had a significant impact on students, including an increased risk of cyberbullying among learners. This study aims to examine how creative learning based on poster-making can integrate digital moral values in the Akidah Akhlak subject as an effort to prevent cyberbullying at MTs Sumbersari Kowang. This study employs a qualitative approach. The results of the analysis indicate that students’ understanding of digital morality remains low because previous learning materials tended to be normative and lacked contextual relevance. Poster-making activities provide opportunities for students to express their understanding creatively, thereby potentially enhancing digital literacy and ethical awareness. Challenges encountered include limited time for teacher guidance, low motivation among some students, and minimal parental involvement in digital supervision. These findings emphasize that poster-based learning can be an effective strategy for preventing cyberbullying if supported by collaboration among schools, teachers, students, and parents